Practices and perceptions of online teaching among faculty of medical colleges - Galidevara, Jyothi; A. S., Veeramani Kartheek; Kedari, Nagarjuna (International Journal of Research in Medical Sciences, 2021)
Background: COVID-19 pandemic has enormously impacted the medical education system owing to a nationwide lockdown. The faculty of medical colleges had to face an abrupt switch from traditional classroom teaching to online teaching methods, which proved challenging. We aimed to evaluate the practices and perceptions of online teaching among faculty of medical colleges. Methods: An online survey tool consisting of socio-demographic variables, teaching experience details, online teaching practices, perceived self-efficacy and training and support received was used. Results: Only 89 of 108 faculty members participated were eligible for the survey. Majority (69.7%) belonged to the age 25-40 years, were Assistant Professors (44.9%) and from Private medical colleges (79.8%) and used Zoom application (71.6%) as their teaching tool. About 16.9% had previous experience of online teaching. Among the teaching practices, content related practices were frequently utilised by the faculty followed by effective communication practices. The overall responses for perceived self- efficacy were above neutral. The faculty received highest and least training/support in content specific knowledge and online classroom management respectively. Linear regression analysis revealed statistically significant positive association of perceived professional and technological self-efficacy with effective communication [(β=0.238, p=0.05), (β=0.510, p<0.001)] and content related practices [(β=0.309, p=0.007), (β=0.477, p<0.001)]. Conclusions: Addressing faculty concerns and appropriate training in the use of digital platforms can help improve online teaching practices thus facilitating effective e-learning. Post-pandemic, a blended classroom and online teaching curriculum would probably provide a better learning environment.